Core and activity-specific functional participatory roles in collaborative science learning - Olli-Pekka Heinimäki; Simone Volet; Marja Vauras (EARLI, 2020)
Prior research on the significance of roles in collaborative learning has explored their impact when they are pre-assigned to group members. In this article, it is argued that focusing on assigned roles downplays the spontaneous, emergent, and interactional nature of roles in small task groups and that this focus has limited the development of generalizable frameworks aimed at understanding the impact of roles in and across collaborative learning settings. A case is built for the importance of focusing on the functional participatory roles enacted during collaborative learning and for conceptualising these roles as emergent, dynamic, and evolving in situ (first claim). Further, a flexible conceptual framework for the analysis and understanding of such roles across diverse collaborative science-learning activities is proposed, based on the assumption that during collaborative learning, both core and activity-specific roles are enacted (second claim). The core roles resemble each other across activities as they associate closely with the nature of the science discipline itself, whereas the activity-specific roles vary across activities as their emergence is dependent on the affordances, demands, and characteristics of the particular activity and environment. Data from three diverse science-learning environments, including four totally or partly student-led collaborative science activities, were scrutinized to establish the degree of empirical support for this assumption and, thereby, the conceptual usefulness of the proposed framework. The contributions of the framework for future research of collaborative science learning are discussed.